Activated mesenchymal stem cell administration inhibits chronic alcohol drinking and suppresses relapse‐like drinking in high‐alcohol drinker rats. (18th October 2017) - Ezquer, Fernando; Quintanilla, María Elena; Morales, Paola; Ezquer, Marcelo; Lespay‐Rebolledo, Carolyne; Herrera‐Marschitz, Mario; Israel, Yedy
Abstract: Neuroinflammation has been reported to follow chronic ethanol intake and may perpetuate alcohol consumption. Present studies determined the effect of human mesenchymal stem cells (hMSCs), known for their anti‐inflammatory action, on chronic ethanol intake and relapse‐like ethanol intake in a post‐deprivation condition. Rats were allowed 12–17 weeks of chronic voluntary ethanol (10% and 20% v/v) intake, after which a single dose of activated hMSCs (5 × 10 5 ) was injected into a brain lateral ventricle. Control animals were administered vehicle. After assessing the effect of hMSCs on chronic ethanol intake for 1 week, animals were deprived of ethanol for 2 weeks and thereafter an ethanol re‐access of 60 min was allowed to determine relapse‐like intake. A single administration of activated hMSCs inhibited chronic alcohol consumption by 70% ( P  < 0.001), an effect seen within the first 24 hours of hMSCs administration, and reduced relapse‐like drinking by 80% ( P  < 0.001). In the relapse‐like condition, control animals attain blood ethanol ('binge‐like') levels >80 mg/dl. The single hMSC administration reduced relapse‐like blood ethanol levels to 20 mg/dl. Chronic ethanol intake increased by 250% ( P  < 0.001) the levels of reactive oxygen species in hippocampus, which were markedly reduced by hMSC administration. Astrocyte glial acidic fibrillary protein immunoreactivity, a hallmark of neuroinflammation, was increased by 60–80% ( P  < 0.001) by chronic ethanol intake, an effect that was fully abolished by the administration of hMSCs. This study supports the neuroinflammation‐chronic ethanol intake hypothesis and suggest that mesenchymal stem cell administration may be considered in the treatment of alcohol use disorders. Abstract : Neuroinflammation induced by ethanol has been proposed to perpetuate alcohol consumption. Present study shows that the administration of anti‐inflammatory human mesenchymal cells (hMSC) into the cerebrospinal fluid of rats that had consumed ethanol chronically inhibited their alcohol intake by 70% and reduced relapse binge‐like drinking by 80%. Astrocyte neuroinflammation induced in hippocampus by chronic ethanol consumption was fully reversed by hMSC administration. Parallel reversal of oxidative stress (GSSG/GSH) is in line with an oxidative stress–neuroinflammation synergy.